Efikasi Burkholderia cepacia GL3 dalam Memacu Pertumbuhan Tanaman Kedelai (Glycine max) - Rumella Simarmata; Harmastini Sukiman (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
Burkholderia cepacia sp. GL3 population naturally occurring in the rhizosphere of Glyricidia sepium was evaluated by metabolic and molecular profiling and for some traits associated with plant growth promoting (PGP) and phosphate solubilizing activity. This research were performed to investigate the effect of inoculation of phosphate solubilizing bacteria (B. cepacia sp. GL3), VAMycorrhizal, Rhizobium bacteria associated with soybean, consortium of potential microbes, combination of PSB and VA-Mycorrhizal, combination of VA-Mycorrhizal and Rhizobium, combination of PSB and Rhizobium, and combination of PSB, VA-Mycorrhizal and Rhizobium with the same concentration toward the growth of soybean plant (Glycine max). The research using polybags with 10 kgs capacity of soil, at the research field of Research center of Biotechnology-LIPI, Cibinong. Parameters used are plant height, number of pods, weight of pods, and weight of seed. This research is experimental research using RAL factorial (10x4). Analysis data using SAS statistic analysis, and then using Duncan test 5%. Results demonstrated that, all treatments displayed significant effect toward plant height, weight of pods, and weight of seed. But it had no significant effect on number of pods. Inoculation of PSB showed significant effect toward plant height, number of pods, weight of pods, and weight of seed as compared to inoculation of VAMycorrhizal and negative control (with chemical fertilizer and uninoculated plant). Percentage increase in soybean seed weight of PSB inoculation plant compare to inoculated plant 47,9%, three months after inoculation. Moreover, the combination of five potential microbes were able to positively affect that showed significantly values of weight of seed, as compared with single microbe inoculation and uninoculated plants. The weight of soybean seed could show productivity of soybean.Keywords: Burkholderia cepacia sp. GL3, growth promotion, phosphate solubilizing bacteria on soybean plant